Cross-Border Cooperation between the Russian Federation and the Republic of Belarus: Development Problems in New Economic and Political Conditions - A. N. Mezhevich; I. P. Sitov (Управленческое консультирование)
The authors consider the economic and political situation around Russia and Belarus in 2022–2023 as new conditions, as well as its influence on relations within the Union State of Russia and Belarus. Border area as a territory adjacent to other states is inevitably involved in international trade and cooperation, but its role can be both contact and barrier, and development is both dynamic and becoming depressed. The article describes the factors of global processes affecting the border and its features on the territory of the Russian Federation and justifies the use of the theory of “center — periphery” for further analysis of the border space between Russia and Belarus. The two states are obliged to build a system of border interaction. This system should be part of a system of supranational governance built to solve the problems of two sovereign states. Cross-border cooperation is not only a managerial, but also an economic resource that will deepen union integration.